Tradhisi Nyekar Ing Pundhen Mbah Putri Ayuing Dusun Wire Desa Gedongombo Kecamatan Semanding Kabupaten Tuban - Wahyu Intan Rahmawati; Sukarman Sukarman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The tradition that has been carried out every year and is believed by the people of Gedongombo Village, Semanding District, Tuban Regency is an activity that cannot be abandoned by the local community. The traditions and habits that are often carried out are the characteristics of the Tuban area. The tradition of nyekar or pilgrimage to the tomb of Mbah Putri Ayu who is the ancestor of the local hamlet is one form of gratitude and respect for the ancestors who have had a great influence on the Wire Hamlet. Mbah Putri Ayu is a descendant of the King of Tuban who was very famous at that time. She has a very beautiful face, is smart and dignified. The focus of the discussion in this study is how the origins, procedures, and ubarampe and the meaning of the ubarampe. This study uses the theory of half-literate folklore from James Danandjaja. The research design uses a qualitative descriptive method to provide a detailed explanation. The data sources used are primary and secondary data, oral data and non-verbal data. The results of the research on the Nyekar Tradition at Pundhen Mbah Putri Ayu in Wire Village, Semanding District, Tuban Regency are related to culture. The traditional activities are supported by local residents ranging from young people to old people.